2020
DOI: 10.1145/3394287
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Tower Construction—A Method to Study the Impact of a Robot’s Allocation Behavior on Interpersonal Dynamics and Collaboration in Groups

Abstract: Research on human-robot collaboration or human-robot teaming, has focused predominantly on understanding and enabling collaboration between a single robot and a single human. Extending human-robot collaboration research beyond the dyad, raises novel questions about how a robot should allocate resources among group members and about what the consequences of such allocation are for a group's social dynamics and outcomes. Methodological advances are needed to answer these questions allow researchers to collect da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 70 publications
(55 reference statements)
0
4
0
2
Order By: Relevance
“…Lokasi Pelaksanaan penelitian dan observasi dilakukan di Talang Jambe Kecamatan Sukarami Kota Palembang.Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Penelitian kualitatif digunakan untuk memahami konteks penelitian dengan mendeskripsikan secara rinci dan mendalam terkait dengan kondisi yang dialami suatu konteks juga apa yang terjadi di lapangan (Jung, 2020). Sumber data, sumber data dapat diartikan sebagai fakta atau keterangan-keterangan yang akan diolah dalam kegiatan penelitian.…”
Section: Metodeunclassified
See 1 more Smart Citation
“…Lokasi Pelaksanaan penelitian dan observasi dilakukan di Talang Jambe Kecamatan Sukarami Kota Palembang.Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Penelitian kualitatif digunakan untuk memahami konteks penelitian dengan mendeskripsikan secara rinci dan mendalam terkait dengan kondisi yang dialami suatu konteks juga apa yang terjadi di lapangan (Jung, 2020). Sumber data, sumber data dapat diartikan sebagai fakta atau keterangan-keterangan yang akan diolah dalam kegiatan penelitian.…”
Section: Metodeunclassified
“…Kim, 2021). Tower dengan 4 kaki sangat jarang di jumpai roboh, karena memiliki kekuatan tiang pancang serta sudah dipertimbangkan konstruksinya (Jung, 2020). Tipe ini mahal biayanya (650 juta hingga 1 milyar rupiah), namun kuat dan mampu menampung banyak antena dan radio.…”
Section: Hasil Dan Pembahasanunclassified
“…When there are disagreements among agents 61 , we plan to explore how agents can negotiate the allocation of tasks and how agent preferences can be considered fairly. Negotiation and consideration of preferences are intended not only to enhance team performance, but also to foster team relationship satisfaction (e.g., see 73 ).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In a series of studies -aimed at exploring the impact of robots on group dynamics and perceptions of fairness [5,8,12] -I investigated how robots' resource distribution behaviors, a phenomenon I termed "machine allocation behavior", affect human interactions. Through the use of a novel tower construction task [12] and the Co-Tetris platform [8], I analyzed interactions in groups and found that unfair resource allocation by robots could lead to tension among team members and affect team performance, highlighting the importance of fair decisions in human-robot collaboration. A key finding from our experiments suggests that team members who receive more resources from an intelligent machine have feelings of empowerment over their teammates.…”
Section: B Building Theory On How Unfair Robot Actions Shape Human Gr...mentioning
confidence: 99%